Factors limiting availability of rangeland for extensive grazing in Chalinze District, Coast Region - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing the major factors limiting access to grazing in the district of Chalinze, Coastal (Pwani) region, Tanzania in 2018.